Folic acid supplementation, birth defects, and adverse pregnancy outcomes in Chinese women: a population-based mega-cohort study. (October 2016) - He, Yuan; Pan, An; Hu, Frank B; Ma, Xu
Abstract: Background: Periconceptional folic acid use has been widely recommended to reduce risk of neural tube defects. However, the effect on other birth defects and adverse pregnancy outcomes, as well as the time window of folic acid use, needs further investigation. Our study aimed to comprehensively assess the effect of periconceptional folic acid use on pregnancy outcomes in a mega-cohort of women of reproductive age. Methods: The China National Free Preconception Health Examination Project (NFPHEP) was established in 2010 to assess couples who planned to get pregnant within 4–6 months for pre-pregnancy risk factors for birth defects, and was a national project for all couples in 31 provinces. We obtained data on folic acid use before and during pregnancy and pregnancy outcomes from women in the project who became pregnant within 1 year after baseline examinations between 2010 and 2015. Women aged 20–49 years who completed pregnancy outcome follow-up in 220 selected counties were included in the study. Multivariate logistic regression models were used to estimate odds ratios (ORs) and 95% CIs with adjustment for covariates. The current study was approved by the Institutional Research Review Board at the National Health and Family Planning Commission and National Research Institute for Family Planning, and all participants gave written consent. Findings: Our cohort consisted of 1 535 066 women. Compared with the 352 099 (22·9%) women who did not take folic acid supplements before and during early pregnancy, 1 182 967 (77·1%) women who did take folic acid supplements had lower odds of total birth defects (OR 0·88, 95% CI 0·78–0·99), neural tube defect (OR 0·45, 0·33–0·61), preterm birth (OR 0·70, 0·69–0·71), miscarriage (OR 0·59, 0·58–0·61), stillbirth (OR 0·75, 0·69–0·81), and neonatal mortality (OR 0·77, 0·70–0·85). Particularly, those who started folic acid use 3 months before their last menstrual period had a significantly lower risk of total birth defects (OR 0·66, 95% CI 0·58–0·76), neural tube defect (OR 0·42, 0·30–0·60), cleft lip (OR 0·48, 0·28–0·81), face malformation (OR 0·62, 0·41–0·98), preterm birth (OR 0·67, 0·66–0·67), low birthweight (OR 0·74, 0·71–0·78), miscarriage (OR 0·53, 0·52–0·54), stillbirth (OR 0·70, 0·64–0·77), and neonatal mortality (OR 0·70, 0·63–0·78) than did those who did not take folic acid. Subgroup analyses also suggested that the protective effects of folic acid supplementation on preterm birth were significantly stronger among women who resided in the south, were of Han ethnicity, had not been exposed to maternal passive smoking, had a body-mass index of less than 24·0 kg/m 2, and were free of pre-pregnancy hypertension or diabetes (all p<0·001). Interpretation: The findings from this mega-cohort of Chinese women of reproductive age demonstrate the protective effect of periconceptional folic acid supplementation on birth defects and adverse pregnancy outcomes, particularly if supplements are taken early before conception. Funding: Five-twelfth National Science and Technology Support Program (number 2013BAI12B01), the operation funds for basic scientific research of the central authorities (number 2015GJM09). We are thankful for the support of all the investigators and participants who contributed to the National Free Preconception Health Examination Project.